The Effect Of The Jigsaw Cooperative Learning Model Assisted By Wordwall Media On Motivation And Science Learning Outcomes In Fourth-Grade - Farah Fathiyah Ramadhani Sultan; Sri Hastati; Erwin Nurdiansyah (ALENA : Journal of Elementary Education, 2026)
Low motivation and learning outcomes of students in Natural and Social Sciences (IPAS) remain a major problem in elementary school learning. The learning process, which tends to be one-way and does not actively involve students, causes a decline in participation and enthusiasm for learning. Based on this, this study aims to determine the effect of applying the Jigsaw cooperative learning model assisted by Wordwall media on the motivation and learning outcomes of fourth-grade students. This study used a one-group pretest-posttest design with 26 students as subjects. The research instruments included observation sheets of teacher and student activities, learning motivation questionnaires, and learning outcome tests. The data were analyzed using validity, reliability, normality, and paired sample t-test. The results showed that the application of the Jigsaw cooperative learning model assisted by Wordwall media could significantly improve student motivation and learning outcomes. Students showed higher motivation categories and increased average learning outcome scores after the application of this model. Thus, the Jigsaw learning model assisted by Wordwall proved to be effective in improving student motivation and learning outcomes in IPAS subjects.